2003
DOI: 10.1597/1545-1569_2003_040_0180_moiwpr_2.0.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Infants with Pierre Robin Sequence

Abstract: Objective Several methods of treating babies with Pierre Robin sequence have been described since the condition itself was first documented in 1923. The main aim of treatment has been to relieve upper airway obstruction. Treatment methods used range from positioning of the baby to invasive surgery. The aim of this article was to describe the assessment, treatment, and monitoring methods used for babies referred with Pierre Robin sequence (PRS). Setting/Patients From December 1995 to May 2000, 22 consecutive pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…Other authors have reported the success of non-invasive methods [12][13][14]. Wagener et al showed that in all cases in their series of 22 patients, a NPA provided adequate airway management [15].…”
Section: Discussionmentioning
confidence: 97%
“…Other authors have reported the success of non-invasive methods [12][13][14]. Wagener et al showed that in all cases in their series of 22 patients, a NPA provided adequate airway management [15].…”
Section: Discussionmentioning
confidence: 97%
“…Children with PRS have both respiratory and feeding difficulties of varying levels of severity [7]; both play a role in determining the severity of their clinical presentation. Failure to thrive has been shown to be strongly correlated with the severity of airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods of treating babies with Pierre Robin sequence have been described since the condition was first documented 9 . The main aim of treatment is to provide relief from the upper-airway obstruction, with attention to feeding the second most-important factor.…”
Section: Discussionmentioning
confidence: 99%